Product Innovation to Support Fishery Tourism Program at Kedonganan Beach, Bali - Rahma Fibriani Dili Putri; I Wayan Mertha; I Ketut Surata (Politeknik Pariwisata Bali, 2022)
The objectives of this study are (1) to identify the tourism potential of Kedonganan Beach, (2) to identify tourism activities that can be carried out to support the development of fishery tourism on Kedonganan Beach, and (3) to develop innovations for the development of new fishery tourism products at Kedonganan Beach, Bali. This study uses a descriptive qualitative approach using a snowball sampling technique. The data were obtained through observation, interviews, document studies and focus group discussions. The results show that Kedonganan Beach has natural tourism, artificial tourism and social tourism potentials. For activities that can be developed such as fisherman thematic photo shoot, beach club, kid’s playground, turtle conservation, gift shop, cooking class, educational tourism, museum, and pesca tourism. The conclusion is that the development of fishery tourism product innovation can be carried out at Kedonganan Beach with proper planning to make Kedonganan Beach a special tourist spot for the fishery region which has fishery tourism attractions and natural tourism activities.